Volumetric microleakage assessment of glass-ionomer-resin composite hybrid materials - Magalhaes, C. S. de; Serra, M. C.; Rodrigues, A. (Quintessence Publ Co Inc, 1999)
Objective: This study was intended to quantify the marginal leakage of three glass-ionomer-resin composite hybrid materials and compare it with the leakage exhibited by a glass-ionomer cement and a bonded resin composite system. Method and materials: Standardized Class V cavities were prepared on root surfaces of 105 extracted human teeth, randomly assigned to five groups of 21 each, and restored with either Ketac-Fil Aplicap, Z100/Scotchbond Multi-Purpose Plus, Vitremer, Photac-Fil Aplicap, or Dyract. The teeth were thermally stressed for 500 cycles and stained with methylene blue. The microleakage was quantified spectrophotometrically, and the data were statistically analyzed with Friedman's test. Results: There were no significant differences in microleakage among the five groups. Restorations of all tested materials showed some marginal leakage in Class V cavities. Conclusion: The microleakage performance of glass-ionomer-resin composite hybrid materials was similar to those of a conventional glass-ionomer and a bonded resin composite system.
Keywords: class V cavity; glass-ionomer cement; glass-ionomer-resin composite hybrid material; marginal leakage; resin composite; volumetric microleakage